The Relationship Between Listening to English Songs and Learning Enjoyment on Students’ Vocabulary Mastery - Pratiwi, Aurilia Lutvena; Suryadi, Suryadi (IJELR: International Journal of Education, Language, and Religion, 2025)
This study examined the frequency of English song listening, the degree of enjoyment children had studying the language, and the relationship between these variables and vocabulary mastery in seventh-grade students at SMPN 10 Serang City. Pre-tests, post-tests, and questionnaires were used to gather data from 104 students using a quantitative approach. The results demonstrated strong validity and reliability (reliability scores: 0,923 for song listening, 0,924 for vocabulary knowledge). The findings demonstrated that regular exposure to English-language music enhances students' vocabulary and adds enjoyment to the learning process. According to the study, including music in English classes can help students' vocabulary grow. It also proposes that more research be done on other variables that might affect learning results.